1995
DOI: 10.1254/jjp.68.297
|View full text |Cite
|
Sign up to set email alerts
|

The Uricosuric Effect in Rats of E5050, a New Derivative of Ethanolamine, Involves Inhibition of the Tubular Postsecretory Reabsorption of Urate

Abstract: ABSTRACT-N-{3-[4 (2",6"-Dimethylheptyl)phenyl]butanoyl}ethanolamine (E5050), a newly synthesized compound, was shown recently to induce uricosuria in humans via inhibition of the postsecretory reabsorption of urate. We examined the effects of this compound on urate excretion in rats loaded with oxonate and compared these effects with those of the uricosuric drugs trichlormethiazide and probenecid. When administered i.p., E5050 (0.3 -15 mg/kg) increased the urinary excretion rate of urate and the ratio of urate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Urinary excretion of uric acid has been well studied in the rats because rats shows a net reabsorption of uric acid in the renal and respond well to agents known to have effect on uric acid excretion in humans (Sugino and Shimada, 1995;Yamada et al, 1999a). In the present study, hyperuricemia induction caused an increase in the urinary excretion of uric acid and the result is in agreement with the previous reports (Johnson et al, 1969;Yonetani and Iwaki, 1983).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Urinary excretion of uric acid has been well studied in the rats because rats shows a net reabsorption of uric acid in the renal and respond well to agents known to have effect on uric acid excretion in humans (Sugino and Shimada, 1995;Yamada et al, 1999a). In the present study, hyperuricemia induction caused an increase in the urinary excretion of uric acid and the result is in agreement with the previous reports (Johnson et al, 1969;Yonetani and Iwaki, 1983).…”
Section: Discussionsupporting
confidence: 93%
“…The active metabolite of pyrazinamide, pyrazinoate has been reported to inhibit the secretion of uric acid at second segment of the proximal convulated tubulues (Sugino and Shimada, 1995;Yamada et al, 1999b). Meanwhile, the uricosuric drugs such as probenecid and benzbromarone inhibit uric acid uptake in the lumen.…”
Section: Discussionmentioning
confidence: 99%
“…The higher dose of potassium oxonate may result in a much higher increase in urinary uric acid level overshadowing the uricosuric effects being investigated (Sugino and Shimada, 1995). Yu et al, (2006) also reported increased excretion of uric acid level in hyperuricemic animals.…”
Section: Discussionmentioning
confidence: 97%
“…We have used a dose of 200 mg of oxonate/kg body weight since a higher dose of the drug would result in a much higher increase in urine urate level overshadowing the uricosuric effects being investigated (Sugino and Shimada, 1995). Potassium oxonate is an inhibitor of uricase.…”
Section: Discussionmentioning
confidence: 99%